Acute high-level toluene exposure decreases hippocampal neurogenesis in rats. (November 2016) - Yoon, Jin-ha; Seo, Heung-Sik; Lee, Jinsoo; Moon, Changjong; Lee, Kyuhong
Toluene is an organic solvent that is used in various industrial applications. Despite its usefulness, toluene has toxic effects on the brain and is a substance that is commonly abused. Toluene causes behavioral and functional abnormalities such as decreased memory capacity, cognitive impairment, and depression-like symptoms. However, the target sites and toxic mechanisms of inhaled toluene in the brain are poorly understood. In this study, we subjected Sprague-Dawley (SD) rats to acute high-level toluene exposure (7000 ppm) to investigate its neuronal toxicity, and in particular, its effect on neurogenesis in the hippocampus. In order to assay the effects of inhaled toluene on hippocampal neurogenesis, we measured the levels of neurogenesis markers Ki-67 and doublecortin (DCX) in the hippocampus 1, 2, 5, and 8 days after cessation of toluene exposure. In addition to assaying clinical signs, body weight, and bronchoalveolar lavage fluid, the liver, lungs, and kidneys were subjected to histopathological examination to investigate the toxic effects of high-level toluene exposure. Although abnormal neurological signs were observed after toluene exposure, these disappeared within 24 h and no toluene-related toxicological effects were observed in the liver, lungs, or kidneys. The animals exposed to toluene showed significantly decreased hippocampal neurogenesis, which persisted until the 8th and final day of measurement. Thus, acute high-level toluene exposure inhibited hippocampal neurogenesis and produced transient abnormal neurological signs, but did not produce toxicity in the other organs studied.